MOLECULAR-SCALE SURFACE PROCESSES DURING THE GROWTH OF CALCITE IN THE PRESENCE OF MANGANESE - Astilleros J.M.; Pina C.M.; Fernndez-daz L.; Putnis A. (My University, 2002)
This paper deals with the growth behaviour of the Mn-Ca-CO3-H2O solid solution-aqueous solution system on calcite {104} surfaces. This system represents a model example, which allows us to study the effect of a number of controlling factors on the crystallisation: (1) the supersaturation function, β(x), and nucleation rate function, J(x), for the Mn-Ca-CO3-H2O system, (2) the relationship of such functions to the molecular scale growth mechanisms operating on growing surfaces, and (3) the surface structure of the calcite {104} faces. In situ atomic force microscopy (AFM) growth experiments revealed a wide variety of surface phenomena, such as the transition between growth mechanisms, anisotropic changes in the step rates, and the influence of the Mn-bearing newly formed surface on subsequent growth (step stoppage followed by the formation of two-dimensional nuclei and the reproduction of the original calcite {104} surface microtopography). These phenomena result from the interplay between the controlling parameters and are explained in those terms.